Experimental Study for the Improvement of Vision Through Side Window of a Car During Rain - Verma, Mukesh (My University, 2015)
Road visibility in passenger vehicle is of major concern for the car manufacturers and safety design engineers. Water film (fog) that forms on the windshield during winter times would reduce and disturb the driver’s visibility. Extreme weather conditions can make a difference while driving. One may experience the wide range of challenges during driving. The factors which mostly affect the visibility can be rain, fog, ice, snow, dust etc. Due to such factors, it becomes very tough for the driver to have a clear view of both sides of the vehicle. Rear view is possible with the help of left and right rear view mirrors fitted outside the front doors. Visibility of rear view mirror depends upon the visibility of the front side window glasses. Driving through rain, produces more challenging situation when water droplets on outside surface of side window glass obstruct the vision through rear view mirrors as well as the left and right side vision at cross roads. This problem becomes more dangerous when light gets scattered through water droplets and obstruct the vision during rainy night. The main objective of this work is to find the possible solution for removing the rain water droplets and fog from a specific area of side window to have a clear view of the side view mirror to avoid the accidents. In the present work, compressed air utilised as a working fluid to impinge on the side glasses with the help of converging nozzles. The various combinations of nozzle design, air velocity and impinging angle are studied for obtaining maximum clearing area. Computer simulated results are verified with the help of experimental results.
ME, MED
Keywords: Rain; Driving; Glass; Cleaning